Environmental sustainability assessment of the risks of some heavy elements associated with the dust storms that struck Baghdad in 2022 - Jasim, Hasan Kattoof; Al-Khafaji, Raad Mahmoud Nasif; Humadi, Adnan Jassam; Jassim, Huda Hadi (Iraqi Journal of Science, 2025)
The results were obtained through a study of three samples of three dust storms that struck the Baghdad Governorate in 2022. The following results were obtained by analyzing the grain sizes, showing that silt and clay are the main parts where the silt portion is occupied. The silt fraction occupies first place with a percentage ranging between 31.8%-51.9% with an average value of 43.22%. The clay fraction comes in second place with a percentage ranging between 31.8%-59.5% with an average value of 48.98%. In contrast, the sand percentage comes Finally, with a relative distribution ranging between 5.6%-11.6 and an average percentage of 7.78%. It was found that the organic matter in the samples of the study area was 1.78 and in the range 1.33 - 2.28 and was classified as medium-humic organic matter. The acidity values of the study area samples ranged between 7 - 8 and at a rate of 7.3, they range from neutral to slightly basic. The percentage of loss on ignition for samples in the study area ranged between 11.6 - 18.66% and 14.44%. The reason for the presence of materials lost in combustion is the presence of various materials, including organic materials, calcium oxides, and sulfates. The presence of silica transported in dust storms in a very small percentage, and the health risks of metals (Cr, As, Ni, and Cd) were evaluated according to USEPA method. Hazard quotient (HQ) and Hazard index (HI) results take the descending order Cr>As>Ni>Cd for children and adults, While the values of carcinogenic hazards (CR) and total cancer risks (TCR) take descending order Cr > Ni >Cd >As.